PENYULUHAN TENTANG UPAYA PENCEGAHAN SERTA POLA HIDUP SEHAT DIMASA PANDEMI COVID-19 DAN BERBAGI MASKER GRATIS DI KOTA PEKANBARU DAN SEKITARNYA - Benni Iskandar; Tiara Tri Agustini; Ferdy Firmansyah; Neni Frimayanti; Armon Fernando; Wildan Khairi Muhtadi (Universitas Pahlawan Tuanku Tambusai, 2022)
At the beginning of 2020, the world was shocked by the outbreak of a new virus, The new type of Corona Virus (SARS-CoV-2) and the disease is called Corona Virus Disease 2019 (COVID-19). It is known that the origin of this virus originated in Wuhan, China, was discovered at the end of 2019. Until now, it has been confirmed that there are 65 countries that have contracted this virus (WHO data March 1, 2020). Among all these countries, Indonesia is one of the countries that is also affected or infected by the Corona virus outbreak. As of April 2020, more than 1000 people have died according to data recorded at the Ministry of Health of the Republic of Indonesia. This is of course a special concern for all circles. This activity aims to provide education about the meaning and dangers of COVID-19 and distribute free masks to the public. The method of implementing this activity is by providing health education about COVID-19 and distributing protective masks for free. People who received education and received masks for free seemed enthusiastic about the service activities being held, it was seen from the seriousness of the community in listening to the material and reading the educational brochures provided.